1997
DOI: 10.1164/ajrccm.156.2.9607005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Early Surfactant Treatment Persisting for One Week after Lung Transplantation in Rats

Abstract: We investigated whether pulmonary surfactant in rat lung transplants recovered during the first week post-transplantation, along with symptoms of the reimplantation response, and whether this recovery was affected by early surfactant treatment. The severity of pulmonary injury was varied by transplanting left lungs with 6-h and 20-h ischemia (n = 12 and 19, respectively). Half of the transplants were treated by instillation of surfactant before reperfusion. Lungs from sham operated, and normal rats (n = 4 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 27 publications
3
27
0
Order By: Relevance
“…Since 1966, experimental data generated in lung transplantation models have provided evidence for surfactant abnormalities and depletion after lung ischemia-reperfusion injury (LIRI) [1][2][3][4][5][6]. In 1998, Hohlfeld and colleagues demonstrated surfactant alterations in human lung transplant recipients, more than 1 year after transplantation [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since 1966, experimental data generated in lung transplantation models have provided evidence for surfactant abnormalities and depletion after lung ischemia-reperfusion injury (LIRI) [1][2][3][4][5][6]. In 1998, Hohlfeld and colleagues demonstrated surfactant alterations in human lung transplant recipients, more than 1 year after transplantation [7].…”
Section: Introductionmentioning
confidence: 99%
“…Because the endogenous surfactant pool is damaged by LIRI, the effect of surfactant replacement therapy has been investigated using experimental models of LIRI [1][2][3][4] addressed only the first few hours after reperfusion and focused mainly on treatment of the recipients. The administration of exogenous surfactant just before or after reperfusion resulted in improved lung function within hours after reperfusion [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, these lung injury sequelae (i.e. high alveolar protein concentration and percentage of neutrophils in BAL) were absent 1 week after transplantation in animals treated with surfactant before reperfusion, but were not observed in untreated rats [9].…”
Section: Discussionmentioning
confidence: 95%
“…The therapeutic dose we used for intratracheal administration of KL 4 surfactant (25 mg?kg body weight -1 ) to donor lungs is ,15% of the dose recommended for surfactant instillation in neonatal RDS (175 mg/kg bw), and much lower than that used for the treatment of patients with ARDS (100-300 mg?kg body weight -1 ) [19] and that previously used in experimental lung transplantation (50-200 mg?kg body weight -1 ) [8][9][10][11][12][13]. We found that a higher dose of KL 4 surfactant (65 mg?kg body weight -1 (2.5 mL?kg body weight -1 ) did not increase the beneficial effect of this synthetic surfactant (data not shown).…”
Section: Lung Transplantationmentioning
confidence: 99%
See 1 more Smart Citation